2013
DOI: 10.1177/0363546513482085
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Medial Patellofemoral Ligament Reconstruction in Young Patients

Abstract: Complications occurred in 16.2% of MPFL reconstruction surgeries for patellar instability in young patients, with almost half resulting from technical problems. Patients should be counseled preoperatively on the risk of potential complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
239
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(251 citation statements)
references
References 41 publications
9
239
0
3
Order By: Relevance
“…A significant percentage of complications associated with MPFL reconstruction occur because of technical errors, which typically involve improper graft position or tension (or both). 15,16 Recurrent instability can occur when the graft is too loose or if fixation on either the femoral or patellar side fails. Conversely, over-tightening or malpositioning of the graft can lead to maltracking, stiffness, and excessive medial compressive forces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant percentage of complications associated with MPFL reconstruction occur because of technical errors, which typically involve improper graft position or tension (or both). 15,16 Recurrent instability can occur when the graft is too loose or if fixation on either the femoral or patellar side fails. Conversely, over-tightening or malpositioning of the graft can lead to maltracking, stiffness, and excessive medial compressive forces.…”
Section: Discussionmentioning
confidence: 99%
“…17 Patellar fracture is a major complication after MPFL reconstruction, and this has been described most commonly after techniques involving patellar bone tunnels. 16,[18][19][20] We are aware of only 2 described MPFL reconstruction techniques involving suspensory adjustable-loop cortical button femoral fixation, 21,22 and this is the first described technique using the TightRope system on the femoral side. Golant et al 21 described knotless suture anchor patellar fixation and the use of a hybrid adjustable-loop cortical button with interference screw fixation on the femoral side.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous methods of graft fixation, both with hardware and hardware free, using variations in drill-hole techniques have been described in the literature. [1][2][3] Regardless of the drill-tunnel technique, however, all of these methods have in common the necessity to breach the integrity of the patellar cortex, the reduction of the patellar bone substance, and the associated potential for subsequent bony complications.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, violation of the chondral surface has also been reported when using a drill-hole fixation technique. [1][2][3] In a systematic re view of the literature, Shah et al 3 found an overall cumulative complication rate of 26.1%, with patellar fracture being one of the major complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation